Continuance Intention For People Needs A Great Services With Their Cars - Pertiwi, R Dewi; Kuswara, Galuh Boga (Jurnal Ekonomi, 2024)
Research purposes is for get results study and analysis about influence quality service to continuity intention through mediation brand images on a service companies maintenance car in Bandung. Research methods This use descriptive verification, with analysis in a way descriptive based from tabulation the results of the research instruments that have been carried out shared to respondents and analysis verification with method analysis track. Population in study This is the people of Bandung who have own experience in service maintenance car, so determined as many as 115 respondents as sample for represent the people of Bandung regarding continuity intention in use service maintenance car. Research result show that Quality service No influential in a way positive and significant to continuity intention in service companies’ maintenance car in Bandung, with mark significance 0.234 > 0.050 and value negative influence of -9.7%. Quality service influential in a way positive and significant to brand images on a service companies maintenance car in Bandung, with mark significance 0.000 < 0.050 and value influence positive amounting to 68.8%. Quality services and brand images influential in a way positive and significant to continuity intention in service companies’ maintenance car in Bandung, with calculated F value 375.411 > F table 3.16 and value influence positive amounted to 87.0%. Brand images influential in a way positive and significant to continuity intention in service companies’ maintenance car in Bandung, with mark significance 0.000 < 0.050 and value influence positive of 92.0%. Brand images can mediate in a way positive and significant quality service to continuity intention in service companies’ maintenance car in Bandung, with mark significance Sobel static test amounting to 9,784 > t table 1,665 and value influence No direct in a way positive amounting to 63.2%.